A bird's eye view of lexical creativity in original vs. translated Slovene fiction. (1st October 2016) - Vintar, Špela
ABSTRACT: This paper addresses lexical creativity and applies corpus-based methods to, firstly, identify potentially creative lexemes and, secondly, compare translations into Slovene from different source languages (English, German, French, and Italian) with texts originally written in Slovene. The primary resource for our work is the Spook corpus of translated and original contemporary literary texts in Slovene. We attempt to capture lexical innovations by way of three methods: by looking into the words occurring only once (hapax legomena); by extracting words that occur in only one of the books; and, finally, by comparing the lexical inventories of original English and translated Slovene texts to large reference corpora EnTenTen and Gigafida, respectively. Our quantitative results imply that translators are at least as creative as authors in coining new words or using unexpected word forms, whereby it seems that the English–Slovene language pair contains the largest number of novel lexical items. The analysis of text-specific word lists reveals the special lexical properties of each single book, including specialised terminology, slang, and dialect vocabulary, as well as author- or translator-specific neologisms, borrowings, and coinings. While these findings cannot be generalised in terms of a prevailing translation strategy, results are encouraging because they show that – at least in our corpus – translators know how to be bold in their lexical choices and do not appear to be inferior to authors in their ability to create new words.